Individual perceptions of HR practices, HRM strength, and appropriateness of care: a meso, multilevel approach - Dello Russo, S.; Mascia, D.; Morandi, F. (International Journal of Human Resource Management, 2018)
We take a meso approach toward investigating the interplay between perceptions of individual employees regarding HR practices and the variability of such perceptions within the department (i.e. HRM strength) and their effects. This study included 2821 healthcare professionals (i.e. nurses, head nurses, technicians, obstetricians and allied health staff) nested in 44 departments of 27 hospitals. Cross-level moderation analyses revealed that individual perceptions of HR practices positively predict individual perceptions of proactivity climate, moderated by HRM strength in the corresponding department. As hypothesized, idiosyncratic perceptions of HR practices predict perceived proactivity when HRM strength is weak because ambiguous situations are interpreted based on direct experience; on the other hand, strong situations reduce the reliance on individual experiences making perceptions of proactivity climate more homogeneous with one another. This enables the emergence of a collective climate for proactivity (i.e. individual perceptions of proactivity aggregated at the department level) which, consistent with our hypothesis, positively predicts appropriateness of care. These findings shed light on the processes by which HR practices are effective and have important implications for HR managers and professionals with regard to extending the involvement of individuals in HR practices.